Application of Compatible Biological Agents to Control Blood Disease Bacteria Causes Blood Disease in Banana Plants at Korong Kampung Guci Padang Pariaman - Linda Advinda; Azwir Anhar; Syahrastani Syahrastani (Pelita Eksakta, 2021)
Control of plant diseases is usually carried out by the community using chemical pesticides. These chemical pesticides can damage the environment and human health. As an alternative, a technique for using fluorescent pseudomonad biological agents has been developed as an antagonistic, environmentally friendly microorganism to reduce the negative impact of using chemical pesticides. Community service has been carried out in Korong Kampung Guci Nagari Lubuk Pandan, Padang Pariaman regarding the application of compatible fluorescent pseudomonad biological agents. After the material was presented to the participants, it was continued with the application of compatible fluorescent pseudomonads to the tissue cultured rhizosphere of banana plants. All participants enthusiastically applied compatible fluorescent pseudomonads in the field.